China’s Banking Industry - Valer Dávila, José Carlos (2012)
The present report will show that in 10 years time, China’s banking industry would still be dominated by Chinese firms. Analyzing the future competitive environment in China’s banking industry, we can see from the different sources that the non-market environment (mainly governmental policy) will drive the trends of the future (see p.18). Thus, only if the government continues to open industries, like banking, to foreign investment (see p.20), will we see an increase from the current 2% market share of multinational banks. In that scenario, Chinese banks could suffer pricing pressure and lower profitability, as seen in China’s banking value chain (see p. 11). For a better understanding of the issue, this report presents an overview of China’s banking industry (brief history, current status of its value chain) and then it highlights trends in both the international and Chinese market environment using scenarios that, as we will see, depend mostly on economic development and stability. The uniqueness of China’s banking industry arises from the institutional voids (immature financial market, poor regulation, large ownerships by government entities, lack of trained professionals, limited financial markets and products, and an inefficient finance allocation due to virtual intermediation monopoly and the capital controls). In order to evaluate if Chinese firms are able to compete with foreign firms in the domestic market (see p.32), I find that the CAGE distances (comparing with the banks in the Asian regions and worldwide averages) are the main obstacles to be overcome by multinational firms. However, multinational banks have the advantage of a more developed financial knowledge that could allow them to ARBITRAGE the immaturity of China’s fee-based business, to ADAPT, not by buying but by investing in the listed shares, or to AVOID the rules by listing foreign banks (dual listing, depositary receipts or A-H share classes), as an HSBC example will show. Finally, I must state that preparing this report has been particularly difficult because of the institutional void of information. For instance, “the numbers say Chinese Banks are doing brilliantly” but the market doubts the veracity of the numbers given the institutional void of poor information and regulation (The economist, 2011).